Agricultural planning and its role in forming the Agricultural System in the ALGAB Region of Naher al-Bared site during the period 1990-2010 (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
agricultural planning needs for the development of the agricultural sector, the study of existing infrastructure and to identify the problems facing the agricultural sector and to propose solutions, and is considered a step to pave the way for the agricultural system, agricultural proposed scientific way based on agricultural planning is needed to achieve specific goals, such as the increase in agricultural production and improve its quality and raise the standard of living of the population, produces agricultural system from the interaction of the elements of agricultural land and population laboratories and markets, if consideration of the territory of the ALGab including owned by the components of the agricultural, such as land, arable land, which for more than 65%, providing irrigation water, such as the Orontes river existing rivers like ALBared river, soil and modern agricultural investment, as well as the population who provide labor and consumer market and at the same time, as well as existing laboratories in the territory of sugar laboratory in Tel Salhab, finally deployed Markets In the territory of the ALGab law such as the market Mhardeh and AL Suqaylabiyah, but is still the level of agricultural planning in the Territory very low, on the one hand distributed dams in the eastern part and the absence of some labs and then from production areas, poor management of irrigation water, the choice of location for the ALBared river for agricultural system, aimed at establishing laboratories in the site of the ALBared river, such as fodder laboratory ,cotton mill and cereals, given the situated close to the agricultural land and infrastructure, and near transport routes of the Chairperson between the Territory and the governorates of the coast and Hamah, thus contributing to the increase in agricultural production and raising the standard of living of the population of the territory of the law of the ALGab.